2020
DOI: 10.1038/s41564-020-0757-2
|View full text |Cite
|
Sign up to set email alerts
|

Genetic circuit design automation for yeast

Abstract: Cells can be programmed to monitor and react to their environment using genetic circuits. Design automation software maps a desired circuit function to a DNA sequence, which requires units of gene regulation (gates) that are simple to connect and behave predictably. This poses a challenge for eukaryotes due to their complex mechanisms of transcription and translation. To this end, we have developed gates for yeast (Saccharomyces cerevisiae) that are connected using RNA polymerase (RNAP) flux as the signal carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
158
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(159 citation statements)
references
References 111 publications
0
158
1
Order By: Relevance
“…Among them, the performance of the DAPG-ON switch was comparable to that of the Tet-ON switch, which is known as one of the best switches in terms of its fold induction (>10 2 ) ( Fig. 5b), as well as that of the recently reported high-performing switches 75 . We then demonstrated that these evolved switches could be further improved in fold induction simply by tweaking the numbers of operators 10 tandemly aligned in synPs.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Among them, the performance of the DAPG-ON switch was comparable to that of the Tet-ON switch, which is known as one of the best switches in terms of its fold induction (>10 2 ) ( Fig. 5b), as well as that of the recently reported high-performing switches 75 . We then demonstrated that these evolved switches could be further improved in fold induction simply by tweaking the numbers of operators 10 tandemly aligned in synPs.…”
Section: Discussionmentioning
confidence: 64%
“…Evidently, adding this sequence to p tetO7 caused significant leakage of the GFP expression ( Supplementary Figure 18). A set of terminators and ribozyme sequences could be used to insulate synPs from their upstream sequences to block their transcription read-through 75 .…”
Section: Discussionmentioning
confidence: 99%
“…However, this could be mitigated by balancing or tuning the expression levels of relevant proteins. Furthermore, synthetic regulatory systems with diverse operational modes 31,32 , such as auto-regulatory feedback loops, toggle switches, and engineered riboswitches, may permit the decoupling or integration of cellular growth and terpene secretion.…”
Section: Main Textmentioning
confidence: 99%
“…The rich information available at the genome, transcriptome, proteome and metabolome levels for these organisms have made them the go-to cells for creating modular DNA part libraries and rapid cloning toolkits that can quickly and easily combine these DNA parts into novel genetic programs [37,38]. Synthetic biology projects in these microbes regularly now involve the design and construction of synthetic DNA programs 10 s and 100 s of kilobases in length, often containing dozens of modular DNA parts and typically with many design variants built and tested in parallel [39,40].…”
Section: Synthetic Biology Toolkits For Bringing New Functionality Tomentioning
confidence: 99%